Functional links between sensory representations, choice activity, and sensorimotor associations in parietal cortex - Chang, Ting-Yu; Doudlah, Raymond; Kim, Byounghoon; Sunkara, Adhira; Thompson, Lowell W; Lowe, Meghan E; Rosenberg, Ari (eLife, 2020)
Three-dimensional (3D) representations of the environment are often critical for selecting actions that achieve desired goals. The success of these goal-directed actions relies on 3D sensorimotor transformations that are experience-dependent. Here we investigated the relationships between the robustness of 3D visual representations, choice-related activity, and motor-related activity in parietal cortex. Macaque monkeys performed an eight-alternative 3D orientation discrimination task and a visually guided saccade task while we recorded from the caudal intraparietal area using laminar probes. We found that neurons with more robust 3D visual representations preferentially carried choice-related activity. Following the onset of choice-related activity, the robustness of the 3D representations further increased for those neurons. We additionally found that 3D orientation and saccade direction preferences aligned, particularly for neurons with choice-related activity, reflecting an experience-dependent sensorimotor association. These findings reveal previously unrecognized links between the fidelity of ecologically relevant object representations, choice-related activity, and motor-related activity.
Keywords: sensorimotor; parietal cortex; choice activity; 3D vision; oculomotor; nuisance variables